2005
DOI: 10.1007/s11062-005-0052-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Behavioral Depression and Chronic Influence of Antidepressants on NMDA/Glutamate Receptor-Mediated Responses of Neurons of the Rat Gyrus Dentatus

Abstract: In studies on superfused slices obtained from the rat hippocampus, we extracellularly recorded field EPSP (fEPSPs), pharmacologically isolated components of these fEPSP, which were related to activation of synaptic NMDA-glutamate receptors, and neuronal responses of the dentate gyrus, which were mediated by activation of extrasynaptic NMDA-glutamate receptors. Recordings were performed in junctions formed by fibers of the medial perforant pathway and dendrites of granular cells of the gyrus dentatus. In the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 28 publications
(31 reference statements)
0
11
0
Order By: Relevance
“…We believe that, similarly to blockers of neuronal NMDA receptors, antidepressants somehow decrease the functional activity of this receptor population. In studies carried out earlier in our laboratory, it was found that under conditions of chronic injections of tricyclic antidepressants (imipramine and maprotiline) into rats, the amplitudes of responses of neurons localized in the dentate gyrus and induced by activation of both synaptic and (especially) extrasynaptic NMDA receptors decreased [37]. Since chronic injections of antidepressants were accompanied by intensification of the expression of neurotrophins and growth factors, we believe that the latter decrease the number of neuronal NMDA receptors.…”
Section: Resultsmentioning
confidence: 61%
“…We believe that, similarly to blockers of neuronal NMDA receptors, antidepressants somehow decrease the functional activity of this receptor population. In studies carried out earlier in our laboratory, it was found that under conditions of chronic injections of tricyclic antidepressants (imipramine and maprotiline) into rats, the amplitudes of responses of neurons localized in the dentate gyrus and induced by activation of both synaptic and (especially) extrasynaptic NMDA receptors decreased [37]. Since chronic injections of antidepressants were accompanied by intensification of the expression of neurotrophins and growth factors, we believe that the latter decrease the number of neuronal NMDA receptors.…”
Section: Resultsmentioning
confidence: 61%
“…To prevent initiation of seizure activity, the CA3 area was eliminated from each hippocampal slice. After this procedure, slices were transferred to an incubation chamber, where they were superfused with a solution of the following composition (mM): NaCl, 124; NaHCO 3 , 26; KCl, 3; KH 2 PO 4 , 1.25; CaCl 2 , 2; MgSO 4 , 1, and glucose, 10. The solution in the incubation chamber (volume 2 ml) was continuously aerated with carbogen; the flow rate through the chamber, temperature, and pH of the solution (saturated with carbogen) were 2 ml/min, 25°C, and 7.3, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…This effect is determined by suppression of the production of mRNA of subunits of these receptors in a few structures of the brain and is reflected in a drop in the amplitude of NMDA EPSP components in neurons of the gyrus dentatus. Manifestations of analgesic activity of antidepressants in the case of neuropathic pains and moderation of the impairment of neurons in the hippocampus and striatum [10][11][12] are also considered to be related to the above-described complex of events.…”
Section: Introductionmentioning
confidence: 99%
“…It was also found that chronic administration of antidepressant drug impairs the function of neuronal NMDA receptors. This is manifested by the inhibition of mRNA NMDA subunit receptors formation in the hippocampus and decreasing of the amplitude of NMDAcomponents of EPSP of dentate gyrus neurons [19,20]. Therefore chronic administration of imipramine may reduce glutamatergic component glucocorticoid neurotoxicity.…”
Section: _______________mentioning
confidence: 99%